Analysis of susceptibility profile of Pseudomonas spp. and prevalence of bacterial samples from the surfaces of dental consulting-rooms - Pietro, Rosemeire C. L. R. [UNESP]; Kashima, S.; Almeida, Ana Marisa Fusco [UNESP]; Silva, C. H P M; Rocha, L. B.; Pádua, J. M.; Lia, R. C C (My University, 2005)
The aim of this research was to evaluate the susceptibility profile of Pseudomonas spp. and the prevalence of bacterial samples isolated from horizontal surfaces surrounding wash-basins used by dentists in several adjoined consulting-rooms, at points next to and at a distance from the basin, before and after surgical procedures. Our results showed a high percentage of Gram-positive cocci and Gram-negative bacilli; 34.66% were Staphylococcus spp. and 30.12% were non-fermentative Gram-negative bacilli among which Pseudomonas spp. (40.90%) was the commonest genus. Analysis of the susceptibility profile of Pseudomonas spp. isolates by determining the minimal inhibitory concentration (MIC) of 14 antibiotics showed a great variation among the strains and high rates of resistance to cefazolin, ceftazidime and aztreonan. Of the 14 antibiotics tested, 59.03% were found to be active against all the environmental isolates. Strains were resistant to aztreonan (62.82%), while susceptibility to third generation cephalosporins was variable.
Keywords: Dental consulting-room; P. Aeruginosa; P. stutzeri; Pseudomonas; Susceptibility; aztreonam; cefazolin; ceftazidime; cephalosporin; disease predisposition; medical research; minimum inhibitory concentration; nonhuman; Staphylococcus